The Practical Rock & Water Garden : A Step-by-Step Guide From Planning and Construction to Plants and Planting - Robinson, Peter (London Hermes House, 2005)
"Everything you need to know to design and construct a successful rock and water features in your garden. Inspirational plans of full-scale rock and water gardens, including a slate rock pool, a rock stream, a cobble fountain, a raised pool and a wildlife pond. Practical advice on materials and construction with step-by-step photographic sequences and cross-sectional illustrations for a range of fountains and other water features. Guidance on planting schemes and techniques, propagating plants and dealing with pests and diseases, as well as buying and introducing fish." Publisher's description.
Include Color Illustration, Index and Acknowledgement
Keywords: Water gardens -- Rock gardens -- Landscape gardening